Find the best solutions to your problems with the help of IDNLearn.com's experts. Our platform provides trustworthy answers to help you make informed decisions quickly and easily.
Sagot :
I will solve your system by substitution.
(You can also solve this system by elimination.)
2x+y=13;5x−4y=13
Step 1: Solve 2x+y=13 for y:
Solve 2x + y = 13 for y
2x + y + -2x = 13 + -2x
(add -2x to both sides)
y = -2x + 13
Step 2: Substitute −2x+13 for y in 5x−4y=13:
5x−4y=13
5x−4(−2x+13)=13
13x−52=13(Simplify both sides of the equation)
13x−52+52=13+52(Add 52 to both sides)
13x=65
(Divide both sides by 13)
13x/13 = 65/13
x = 5
Step 3: Substitute 5 for x in y = −2x+13:
y = −2x+13
y = (−2)(5)+13
(Simplify both sides of the equation)
y = 3
Answer: x= 5, y= 3
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. For clear and precise answers, choose IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.